Bioanthropological analysis of Békés 103 (Jégvermi-kert, Lipcsei-tanya), a Bronze Age cemetery from southeastern Hungary - Paja, László; Duffy, Paul R.; Parditka, Györgyi M.; Giblin, Julia I. (Acta Biologica Szegediensis, 2016)
The analysis of human skeletal remains is an important tool for reconstructing aspects of health, diet, disease, and population structure (such as demographics, life expectancy, and mortality) in past populations. This study presents the recovery techniques and initial bioanthropological analysis of cremation and inhumation burials from the archaeological site of Békés 103, a Bronze Age cemetery located in southeastern Hungary. In all possible cases, analysts microexcavated cremation urns in a laboratory setting to ensure recovery of all fragmentary skeletal material and allow detailed spatial documentation of each burial’s contents. This report presents estimated age and sex information for each individual, provides a preliminary assessment of observable trends in the population, and offers a paleodemographic profile of the cemetery for comparison with contemporary prehistoric communities in Hungary.